2018
DOI: 10.1163/15736121-12341349
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Death by Tornado: Religiosity and the God-Serving Bias

Abstract: Two self-report experiments examined how religiosity affects attributions made for the outcome of a tornado. Undergraduate students (N = 533) and online adults (N = 537) read a fictional vignette about a tornado that hits a small town in the United States. The townspeople met at church and prayed or prepared emergency shelters for three days before the tornado; either no one died or over 200 people died from the tornado. Participants made attributions of cause to God, prayer, faith, and worship. In both studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Individuals who possess positive religious coping strategies are less disturbed by the aftermath of disasters and more resilient (Johnson, Aten, Madson, & Bennett, ; O’Grady et al, ; Smith, Pargament, Brant, & Oliver, ). Of particular relevance to this study, past experimental research using a fictional tornado vignette found that religious individuals make more attributions to God, prayer, faith and worship to explain why people survive tornadoes, compared to agnostic individuals, but only when no one died (Riggio et al, ).…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Individuals who possess positive religious coping strategies are less disturbed by the aftermath of disasters and more resilient (Johnson, Aten, Madson, & Bennett, ; O’Grady et al, ; Smith, Pargament, Brant, & Oliver, ). Of particular relevance to this study, past experimental research using a fictional tornado vignette found that religious individuals make more attributions to God, prayer, faith and worship to explain why people survive tornadoes, compared to agnostic individuals, but only when no one died (Riggio et al, ).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Additionally, religious leaders often provided spiritual and emotional care in the aftermath of disasters (Entwistle, Moroney, & Aten, ). Religious individuals make more attributions to God, prayer, faith and worship to explain why people survive tornadoes compared to agnostic individuals (Riggio et al, ). Still, it is unknown how religiosity and emotional coping may affect how people respond government messages during disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental research has indicated a 'God-serving bias' in attribution among Christians with strong beliefs in an active, intervening superhuman agent. They are less inclined to attribute events with negative outcomes to that agent, as compared to events with positive outcomes (Riggio et al 2018). Views on death by COVID-19 and martyrdom may testify to another means to achieve the same end: a reinterpretation of the outcome as not negative but positive.…”
Section: Interpreting the Virus: Divine Intentions And Divine Agencymentioning
confidence: 99%
“…Research has shown that religious individuals often invoke divine forces and will when seeking to explain negative, unanticipated, and highly impactful events such as natural disasters (Riggio et al, 2018). While this has previously been investigated in the context of earthquakes (Sibley & Bulbulia, 2012) and hurricanes (Aten et al, 2012), pandemics such as COVID-19 seem likely to function in a similar way.…”
Section: Religion the Search For Meaning And Well-beingmentioning
confidence: 99%